ANALISIS PENGARUH CAPITAL FLOW TERHADAP NILAI TUKAR DAN INDEKS HARGA SAHAM GABUNGAN (IHSG) TAHUN 2011 — 2014 - Herry Budisusetyo (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2015)
This study aims to see the effect of net capital flow on rupiah exchange rate and Composite Stock Price Index (IHSG) in Indonesia. The type of data is time series period January 2011 until December 2014. Analysis technique used is single linear regression. The result of thif research is positive and significant influence of net capital flcw to rupiah exchange rate and composite share price index in Indonesia.